Temperature Influences Herbivory and Algal Biomass in the Galápagos Islands - Carr, Lindsey A.; Gittman, Rachel K.; Bruno, John F. (Frontiers in Marine Science, 2018)
Temperature can influence trophic interactions via predictable effects on the metabolism of ecothermic consumers. Under some conditions, warming should increase top–down control and trophic transfer rates, leading to declines in prey populations. We tested this prediction in the Galápagos Islands, an equatorial upwelling region, where water temperatures are highly variable and nutrient availability is thought to control primary production and standing algal biomass. We used grazing assays, field surveys, and a herbivore exclusion experiment to test the hypothesis that grazing rate and algal biomass are, in part, regulated by temperature via the temperature–dependence of herbivory. Grazing rates were greater during the warm season for urchins and other consumers (including fishes, turtles, and iguanas). Field surveys at ten sites over five years found that temperature was strongly negatively related to macroalgal cover. The results of the exclusion experiment indicate that herbivores had a large effect on macroalgal biomass, even during intense upwelling. Our results suggest that in shallow subtidal habitats across the Galápagos archipelago, grazing pressure increases with temperature, potentially resulting in reduced algal biomass when upwelling is weak and greater algal biomass when upwelling is strong and water is cold; an alternative explanation for widely observed association between upwelling intensity and algal biomass.